The Geography of War and Peace 2004
DOI: 10.1093/oso/9780195162080.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

The Political Geography of Conflict : Civil Wars in the Hegemonic Shadow

Abstract: The attack by the United States on Iraq in March 2003 was atypical of contemporary conflicts. While the attempt to kill Saddam Hussein on March 19 marked the opening of hostilities and was broadcast worldwide instantaneously, a much more destructive conflict that had raged for five years in the Democratic Republic of the Congo continued to receive hardly any notice. The war to depose the Hussein regime resulted in fewer than 12,000 dead (122 U.S. and U.K. troops, 6,000–7,000 civilians, and about 5,000 Iraqi mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In many cases, islands have a history of colonisation or are still considered to be colonies (Lutz, 2009). The literature has focused on US military bases around the world, highlighting post-Cold War geopolitical strategies (Johnson, 2004;O'Loughlin, 2005) as new forms of imperialism and colonisation (Gerson, 2009;Noenoe, 2004) accompanied by economic power strategies (Vine, 2009). In this context, the study of civil-military relations can concern resistance, protests and collective actions (McCaffrey, 2002) led by autochthones and sometimes supported by transnational networks.…”
Section: Sardinia Militarisation An Island Among Many Othersmentioning
confidence: 99%
“…In many cases, islands have a history of colonisation or are still considered to be colonies (Lutz, 2009). The literature has focused on US military bases around the world, highlighting post-Cold War geopolitical strategies (Johnson, 2004;O'Loughlin, 2005) as new forms of imperialism and colonisation (Gerson, 2009;Noenoe, 2004) accompanied by economic power strategies (Vine, 2009). In this context, the study of civil-military relations can concern resistance, protests and collective actions (McCaffrey, 2002) led by autochthones and sometimes supported by transnational networks.…”
Section: Sardinia Militarisation An Island Among Many Othersmentioning
confidence: 99%
“…And they tend to treat the territories of small wars as homogeneous (O’Lear and Diehl, 2007). In other words, these models ignore the geography of violence in small wars, which includes: the spatial dynamics of warfare, fighting, exploitation and coercion; the differentiations of ‘opportunities' and economic incentives across different resource types and actor categories; the time-space dynamics of accumulation and protection and their effects on small war dynamics and the transnational dimensions of small wars and insurgent financing (Ballentine and Sherman, 2003; Buhaug, 2007; Dalby, 2007; Flint, 2005; Gregory and Pred, 2007; Korf and Engeler, 2007; Le Billon, 2007; O’Lear and Diehl, 2007; O’Loughlin, 2005; O’Loughlin and Raleigh, 2007).…”
Section: The Geography Of Opportunity Feasibility and Predation In Small Warsmentioning
confidence: 99%
“…Although this research field (‘ethnicity, natural resources and violent civil conduct’) has been identified by the Times Higher Education in 2009 as one of the top 10 research fronts in the social sciences (Wrigley and Overman, 2010: 5, Table 4), it has remained a rather marginal field within the study of the geographies of war and peace. 3 John O’Loughlin (2005) reminds us that these types of war have often occurred in a ‘hegemonic shadow’ and scholarly attention among geographers has mainly focused on the ‘hot wars' (Flint, 2005: 3) that occurred after 9/11. Only more recently have some contributions started to attend to the geography of ‘resource violence’ - to the spatialities and temporalities of resource exploitation and their entanglements with violent conflict.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation